UPPER MANTLE STRUCTURE BENEATH THE AZORES HOTSPOT FROM FINITE-FREQUENCY SEISMIC TOMOGRAPHY - Yang T.; Shen Y.; van der Lee S.; Solomon S.C.; Hung S.-H. (My University, 2006)
The Azores archipelago is a classic expression of a hotspot that has interacted with a mid-ocean ridge. A variety of geochemical studies and geophysical observations point to the influence of some sort of mantle plume on the formation of the Azores Plateau and the adjacent Mid-Atlantic Ridge (MAR), but the mantle structure beneath the Azores has not heretofore been imaged tomographically at a sufficiently fine resolution to resolve a narrow plume. We present a P-wave velocity model of the mantle beneath the hotspot derived from teleseismic body waves recorded by six broadband seismic stations on the Azores Islands including the Global Seismographic Network station CMLA. Three-dimensional travel-time sensitivity kernels are used to account for the effects of wavefront healing and scattering of seismic waves. An inversion of 228 P-wave travel-time delays reveal a low-velocity anomaly in the shallow mantle (less than 200 km deep) along the Azores archipelago and beneath the Azores Plateau (centered approximately at 38.5°N, 28.5°W). The low-velocity anomaly extends northeastward and downward to connect to a plume-like column of low-velocity material from ~ 250 km to at least 400 km depth centered northeast of Terceira. These results are consistent with other geophysical and geochemical observations and provide seismic evidence for a model of plume-ridge interaction in which the plume conduit is deflected to the southwest in the shallow mantle by asthenospheric flow and plate motion and contributes hot mantle material and excess melt to the MAR south of the Azores. © 2006 Elsevier B.V. All rights reserved.
Keywords: AZORES; FINITE-FREQUENCY TOMOGRAPHY; HOTSPOT; MANTLE PLUME; MID-ATLANTIC RIDGE; PLUME-RIDGE INTERACTION; TRIPLE JUNCTION